System of stimulation and record of the eye movement with the use of infrared videoculography - Fredes Hubert Sánchez; Talía Vázquez Romaguera; Carlos Román Vázquez Seisdedos (Centro Provincial de Información de Ciencias Médicas, 2020)
The analysis of eye movements allows to diagnose neurodegenerative, neuropsychiatric and neuroophthalmologic diseases, among other that affect the individual social performance. In this analysis the use of videoculography is gaining in importance worldwide, due to its structural simplicity, precision and long term economic feasibility. In this respect, the objective of this investigation was to develop and evaluate a system of visual stimulation and record of the eye movements. The system in question allowed to obtain ocular images with good resolution (2 megapixels), clarity and contrast that facilitated its later processing. In a same way, the tests of stimulation by means of the sacadic patterns use with amplitudes between 30º and 60º to the 0,5Hz frequency allowed to obtain with enough quality the images recorded and to verify that the eye movements of the pupil center follow these patterns very closely.